Binary LDPC Codes Decoding Algorithm Based on MRF and FPGA Implementation - Zhongxun Wang; Wenqiang Wu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The improved LDPC code decoding algorithm mainly refereed to improving decoding performance or reducing the decoding computation complexity. No matter hard decision or soft decision LDPC code decoding algorithm, we can get all ring number by one test, instead of testing each long ring number, after optimizing ring detection algorithm. We putted forward the application of Gaussian Markov Random Field model to realize the source parameter estimation, and make logarithmic likelihood ratio correction of bit sequence received by the channel decoding end. Joining source residual redundancy information to increase the decoder error correction ability. Source estimation adaptive variable can correct coefficient, and it was regulated by error rate. Under the condition that computational complexity increasedlittlely, the LDPC code decoding algorithm based on MRF effectively improved the decoding performance and implemented the improvement of LDPC code decoding algorithm .In the end, we realized the decoding algorithm by using FPGA.